1983
DOI: 10.7863/jum.1983.2.11.515
|View full text |Cite
|
Sign up to set email alerts
|

Klippel-Trenaunay-Weber syndrome: appearance in utero.

Abstract: We were able to detect hemihypertrophy of a fetus in a routine prenatal ultrasound examination. The presence of hemangiomas and varicose veins in the hypertrophied left lower extremity at birth enabled us to diagnose the Klippel-Trenaunay-Weber syndrome. The possibility of a congenital arteriovenous fistula causing the constellation of findings was ruled out by a nuclear flow study and a thorough physical examination. A computerized tomographic scan revealed that the hemangiomas were superficial in the hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

1990
1990
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 2 publications
0
14
0
Order By: Relevance
“…There are several reports of the prenatal sonographic findings, first described in 1981 with the cutaneous haemangiomata appearing sonographically as multiple echolucent areas (Hatjis et al, 1981). In 1983, a second prenatal case was described reporting hemihypertrophy of a lower extremity (Warhit et al, 1983). There have been scattered case reports of the prenatal sonographic appearances of Klippel-Trenaunay-Weber syndrome subsequently (Shalev et al, 1988;Seoud et al, 1984;Lewis et al, 1986;Meholic et al, 1991;Yankowitz et al, 1994;Jorgenson et al, 1994), with variable fetal and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of the prenatal sonographic findings, first described in 1981 with the cutaneous haemangiomata appearing sonographically as multiple echolucent areas (Hatjis et al, 1981). In 1983, a second prenatal case was described reporting hemihypertrophy of a lower extremity (Warhit et al, 1983). There have been scattered case reports of the prenatal sonographic appearances of Klippel-Trenaunay-Weber syndrome subsequently (Shalev et al, 1988;Seoud et al, 1984;Lewis et al, 1986;Meholic et al, 1991;Yankowitz et al, 1994;Jorgenson et al, 1994), with variable fetal and neonatal outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since that time, 140 to 200 cases have been reported, the majority of which were diagnosed after birth. 2,4 We found only 7 articles in the literature diagnosing the syndrome antenatally. Meholic et al 5 found that the sonographic diagnosis depends on cutaneous or subcutaneous sonolucent lesions and limb hypertrophy.…”
Section: Discussionmentioning
confidence: 95%
“…KTW can affect any part of the fetal anatomy but most often is identified on the torso, buttocks, or lower extremity. 1 Typical presentation of KTW is asymmetric limb hypertrophy usually involving a leg. 2 There is increased arterial flow to the affected area that may be confirmed with color flow Doppler.…”
mentioning
confidence: 99%